Midiatização e relacionamento mercadológico na cibercultura: O estudo de caso do Nike Plus - Barros, Ana Cirne Paes de (2012)
The relationship which has been established in the cyberculture between companies and their audience has been characterized as a communicational phenomenon redesigned from the practices provided by cyberculture, as well as by the process of mediatization. More than a relation of products and services purchase and sale, marketing relationship in contemporary communication presents itself as a long term and intense relationship between participants. Now companies constant search for profits results in concerns about communication flows, with the participation of consumers and, consequentely, with the relationship with their consumers. This situation happens due to the release of the emission, connection and world conversation, considered as the principles of cyberculture, which have allowed marketing relationships in the web as a trend in digital medias, which, in turn, appeal to the inclusion of brands as lovemarks . Nike Plus project, case studied in this work, represents these phenomena by enhancing the exchange of information, the interaction and the affective involvement between company and participant consumers. By relating consumerism and cybercultural communication with marketing relationship, we aim at understanding the benefits for the parties involved and the implicit conditions in this relationship, besides identifying in which ways and aspects Nike Plus is included in relation to companies and its audience. Thus, studies about mediatization (practices which mediatize society s daily life and expand media performance by creating a new environment) are essential to contextualizing the present culture of participation, which, in turn, implies in a broader performance rather than mere consumerism of communication contents by consumers. For these reasons, there is a change in the relationship established with the companies, as well as with the own consumerism culture. Based on this perspective, we focus on Nike Plus case study, as an evidence of a phenomenon which has gained momentum in cyberculture, by representing the comtemporary settings of communication and consumerism.